EFFECT OF IPSILATERAL TESTICULAR TORSION ON THE QUALITY OF SPERM IN CONTRALATERAL TESTIS OF RAT (Rattus norvegicus) WISTAR STRAIN - Ridho, Muhammad Rasyid; Ismy, Jufriady (Indonesian Journal of Urology, 2024)
Objective: This study aims to identify the effect of testicular torsion on the quality of sperm which include: concentration, morphology, and motility of the contralateral testis Rattus norvegicus. Material & Methods: This study is an experimental laboratory study with a post-test only control and completely randomized design (CRD) and divided into 3 groups: control (KO) and treatment (P1 and P2). The treatment group induced testicular torsion of 360˚ to the left for 4 hours. Each group consisted of 9 rats were observed immediately after detorsi (rapid effects) and 9 rats were observed after 30 days do detorsi (slow effect). Data were analyzed by ANOVA - One way and followed by Tuckey HSD test. Results: The results showed a significant difference ( P < 0.05 ) the concentration and morphology of spermatozoa between the control and treatment groups but there is no real difference between P1 and P2 . As for sperm motility are no significant differences ( P < 0.05 ) for each treatment . Conclusion: Based on this it can be concluded that testicular torsion lead to changes in concentration , motility , and morphology of spermatozoa contralateral testis. Keywords: Testicular torsion, quality of sperm, Rattus norvegicus.